Cross Validation of FY3D MWRI Passive Microwave LST With MODIS LST Under Clear-Sky Conditions - Yuting Gong; Huifang Li; Xiuqing Hu; Huanfeng Shen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Passive microwave (PMW) land surface temperature (LST) is widely used in climatology, agriculture, and environmental science due to its large range, all-weather capabilities, and other unique advantages. FY3D microwave radiation imager (MWRI) offers some of the global rare PMW LST products, but the accuracy is not clear due to the lack of research on the validation of the FY3D MWRI LST products. Therefore, cross validation of FY3D MWRI LST with moderate-resolution imaging spectroradiometer LST was investigated in this study. Based on the quality control, temporal matching, and spatial matching, the spatial and temporal distribution were validated between the two LST products from 2019 to 2023. In the spatial cross validation, the overall correlation coefficient (R) of the two daily LST products distributed between 0.68 and 0.84, and the deviation ranged from 3 to 8 K. The R of the two LST monthly products was between 0.78 and 0.89, with the deviation mainly distributed between 3 and 6 K. This suggests that the monthly product is more stable and has a more reliable accuracy than the daily FY3D MWRI LST product. In the temporal cross validation, the seven dominant global land cover types were analyzed. It can be found that the main distribution of R was in the range of 0.7–0.9, and the deviation was mainly 3–6 K. With the improvement of the FY3D MWRI LST official retrieval algorithm, the accuracy of the FY3D MWRI LST products has improved significantly, and the products deserve extensive attention.